2016
DOI: 10.1002/2016ja022364
|View full text |Cite
|
Sign up to set email alerts
|

Spectral evolution of helical electron magnetohydrodynamic turbulence

Abstract: Properties of turbulence in space plasmas above and below the proton gyroscale are very different and different descriptions should be used for the large and the small scales. On scales larger than the proton gyroscale, we can treat the plasmas as conducting fluids and use magnetohydrodynamics (MHD). However, on scales smaller than the proton gyroscale, we cannot use MHD due to various kinetic effects. Electron magnetohydrodynamics (EMHD) is a simple fluid‐like model for small‐scale plasmas. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…2018), as argued on the basis of a Fjørtoft (1953) argument in HRMHD (Schekochihin et al. 2009) and observed in the numerical simulations of EMHD (Cho & Kim 2016). In contrast, if the energy spectra are prescribed at large scales, the transfer rates can adjust freely.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…2018), as argued on the basis of a Fjørtoft (1953) argument in HRMHD (Schekochihin et al. 2009) and observed in the numerical simulations of EMHD (Cho & Kim 2016). In contrast, if the energy spectra are prescribed at large scales, the transfer rates can adjust freely.…”
Section: Resultsmentioning
confidence: 70%
“…Differently, if the dissipation scale is smaller than the ion transition scale where dispersion starts acting, the above model displays unphysical features. This results from the conflict between a prescribed cross-helicity flux in the forward direction and the tendency of the cross-helicity which, at the dispersive scales, identifies with the magnetic helicity, to undergo an inverse cascade Passot et al 2018), as argued on the basis of a Fjørtoft (1953) argument in HRMHD (Schekochihin et al 2009) and observed in the numerical simulations of EMHD (Cho & Kim 2016). In contrast, if the energy spectra are prescribed at large scales, the transfer rates can adjust freely.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of extra invariants does open the possibility of dual or even triple cascades in Hall-RMHD turbulence: in particular, will cascade to larger scales if it is injected at small scales (see S09–§ F.6; Cho & Kim 2016 and references therein), whereas is expected to cascade forward, together with the free energy (Chen, Chen & Eyink 2003; Banerjee & Galtier 2016). Thus, the Hall-RMHD system can offer some considerable rewards to a devoted turbulence theorist.…”
Section: Reduced Dynamics and Heating In The Hall Limitmentioning
confidence: 99%
“…Numerical attempts to model imbalanced turbulence in the MHD regime have proven difficult due to questions about the effects of varying dissipation prescriptions, limited dynamic ranges of accessible simulation domains, and limited run times (Beresnyak & Lazarian 2009Perez & Boldyrev 2010b,a;Perez et al 2012;Mason et al 2012). Some studies have extended beyond standard MHD to the relativistic MHD regime 𝜎 1 (Cho & Lazarian 2014;Kim & Cho 2015), made approximations of large ion-to-electron mass ratio to model scales below the proton gyroradius (Cho & Kim 2016) or to capture finite Larmor radius effects (Meyrand et al 2020), or employed a diffusive model to study turbulence from fluid to sub-ion scales (Miloshevich et al 2020). However, few numerical studies have modeled the fully kinetic collisionless regime-those with an eye towards the solar wind (Grošelj et al 2018)-and none to our knowledge have examined the ultrarelativistic, collisionless regime relevant to highenergy astrophysical systems.…”
Section: Introductionmentioning
confidence: 99%